COSTS OF TRANSACTIONAL E-GOVERNMENT SYSTEMS - Al-Sebie, Madi (European Scientific Journal, ESJ, 2014)
Passing through the different stages of e-government systems, the transactional stage could be considered as one of the most important in the implementation of an e-government system because it represents the highest level of interaction within organisations and between customers and government organisations. The importance of the transactional stage of the egovernment system and its positive impact refers to not only to making the delivery of external services quicker, but also to increasing the efficiency of internal government processes. Consequently, government organisations might seek to reach this stage. However, in order to reach the transactional stage of e-government, there are various dimensions related to government organisations; these dimensions could be challenges, costs or benefits. In fact, there is a lack of studies focusing on the identification of the levels and categorisation of transactional e-government costs. Therefore, this paper will try to fill the information gap based on empirical case studies of two government organisations. This paper will identify the levels and categorisation of transactional e-government costs. Consequently, the work of decision-makers in government organisations will be improved as well as the researchers understanding of transactional e-government costs will be enhanced.